Towards a possible future solution against Multidrug Resistance: An in silico exploration of the Multidrug and Toxic compound Extrusion (MATE) transporter proteins as potential antimicrobial drug targets - Damji, Amira Mahamood (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
The rise of multidrug resistance (MDR) has become a pressing global issue, hindering the treatment of cancers and infectious diseases, and imposing a burden on healthcare systems and the economy. The Multidrug and Toxic compound Extrusion (MATE) superfamily of membrane efflux transporters is one of the key players contributing to MDR due to their ability to export a wide range of cationic and hydrophilic xenobiotics, including treatment drugs, from cells, diminishing their efficacy. Targeting MATE transporters holds great promise in achieving some cellular control over MDR, but first, a deeper understanding of their structure-function-dynamics link is required. This study aimed to explore the MATE transporters as potential antimicrobial drug targets using a two-fold in silico approach. First, virtual screening of compounds from the South African Natural Compounds Database (SANCDB) was performed to identify prospective lead inhibitory compounds against the MATE transporters using molecular docking, and top hits were selected based on their binding energy and interaction with the active site on the N-lobe of the protein. Second, to investigate the molecular-level dynamics of their extrusion mechanism, the MATE transporter structures were embedded in a POPC membrane bilayer using the CHARMM-GUI online tool and then subjected to MD simulations for 100 ns with the CHARMM 36m force field using GROMACS. The resulting trajectories were evaluated using three standard metrics "“ RMSD, RMSF, and Rg; significant global structural changes were observed and key functional regions in both membrane- and non-membrane transmembrane (TM) segments were identified, containing more dynamic and flexible residues than other regions. Furthermore, the MATE transporters showed more of a loosely-packed structure, providing flexibility to allow for conformational switching during their substrate-transport cycle, which is typical for proteins whose secondary structures are composed of all Î±-helices. The scope of this study lied in the preliminary stages of the computer-aided drug design process, and provided insights that can be used to guide the development of strategies aimed at regulating or inhibiting the function of the MATE transporters, offering a possible future solution to the growing challenge of MDR.
Keywords: Multidrug resistance; Multidrug and toxic compound extrusion family, eukaryotic; Docking; Molecular dynamics; Drug development; Transmembrane protein